Social-Emotional Learning in Rural Zambia: A Qualitative Study of Educator Perspectives in the Zambezi District - Zeisner, Catherine (Cross-Cultural Education Studies, 2026)
Social-emotional learning (SEL) and psychosocial support (PSS) are increasingly recognized as foundational to holistic student development, yet research from rural sub-Saharan African contexts remains critically underrepresented in the global literature. This qualitative case study investigated how PK–12 educators in Zambezi, Zambia, understood, practiced, and experienced SEL and PSS. Data were collected through semi-structured interviews, focus groups, and document review with 46 participants, including classroom teachers, guidance counsellors, head teachers, and district leaders across four schools in the Zambezi School District. Findings revealed that while Zambian students experience significant psychosocial stressors, including poverty, exhaustion, hunger, and lack of basic resources, educators showed limited formal knowledge of SEL and PSS frameworks, with nearly all participants reporting no meaningful professional development in these areas. Despite this gap, educators were actively supporting student well-being through culturally embedded practices rooted in the African philosophy of Ubuntu, family engagement, religious community, and a collective belief in education as a pathway out of poverty. These indigenous factors represent theoretically significant contributions to the global SEL literature, challenging Western-dominated frameworks and offering a culturally grounded model of student resilience. The study recommends that the Zambian Ministry of Education, international organizations, such as Regional Psychosocial Support Initiative (REPSSI), teacher training institutions, and district leaders take immediate, coordinated, and culturally responsive action to formalize SEL and PSS training, improve technology infrastructure, and integrate Ubuntu-based frameworks into national education policy.